Upheaval buckling of pipelines - Adebanjo, Oluwatomisin; Simms, Nigel J. (Open University, 2016)
UPHEAVAL BUCKLING OF OFFSHORE pipelines occurs as a result of axial compression induced along the pipelines due to large temperature differences and high internal pressures. This paper aims to research the causes of upheaval buckling, give an overview of the analytical methods, and develops an Excel spreadsheet for initial assessment. Several models of upheaval buckling have been identified and discussed, such as those based on idealized or perfect pipelines, which are related to the railway track analysis and those based on imperfections. The buckle temperatures of the perfect pipelines are proportional to the buckle lengths and axial forces. With the consideration of imperfections, buckle temperatures become inversely proportional to the imperfection heights, therefore larger imperfections would require smaller temperatures to propagate upheaval buckling. Increasing the downward load on the pipelines aids the prevention of upheaval buckling. Also, relevant methods to mitigate against the occurrence of upheaval buckling have been discussed. The use of finite-element analysis which considers the seabed profile and plastic deformation of pipe wall would be suitable for precise analysis.